The Global Age-Friendly Community Movement : a Critical Appraisal. - Stafford, Philip B. (Life Course, Culture and Aging: Global Transformations Ser., 2018)
The age-friendly community movement is a global phenomenon, currently growing with the support of the WHO and multiple international and national organizations in the field of aging. Drawing on an extensive collection of international case studies, this volume provides an introduction to the movement. The contributors - both researchers and practitioners - touch on a number of current tensions and issues in the movement and offer a wide-ranging set of recommendations for advancing age-friendly community development. The book concludes with a call for a radical transformation of a medical and lifestyle model of aging into a relational model of health and social/individual wellbeing.